The effect of hetero- and homosexual experience and long-term treatment with fluoxetine on homosexual behavior in male rats - Habr-Alencar, Soraya F.; Dias, Renata G.; Teodorov, Elizabeth; Bernardi, Maria Martha (Springer, 2006)
Introduction the selective serotonin reuptake inhibitors have become the most frequently prescribed drugs for the treatment of depression. Sexual side effects have been noted to occur with this treatment on heterosexual behavior in rats. Heterosexual experience facilitates sexual orientation of male rats and decreases the latencies to first mount and first intromission. on the other hand, homosexual behavior in male rats induced by female hormones has not been evaluated.Aim the objective of this work is to evaluate the effects of heterosexual and homosexual experience in male rats long-term treated with fluoxetine (FLX) on homosexual hormone-induced behavior.Materials and Methods Male rats were treated with FLX or saline solution (10 mg/kg for 65 days). At days 36, 50, and 65 of the treatment, the rats were evaluated for homosexual behavior. Other rats treated with FLX or saline solution for 60 consecutive days were submitted to heterosexual behavior at 14, 21, and 28 days of the treatment. After this, they were orquiectomized and homosexual hormone-induced behavior was observed at 45 and 60 days of the treatment.Results (1) Only treatment with FLX did not affect the homosexual behavior. (2) the homosexual experience facilitated the homosexual behavior mainly on the animals from the control group. (3) the heterosexual experience facilitated the homosexual behavior on both groups.Conclusions Only long-term administration of FLX does not interfere with the homosexual behavior in male rats. The homosexual and the heterosexual experience facilitated the homosexual behavior on the control and experimental groups. We suggested that learning aspects related to sexual behavior are responsible by these results.
Keywords: fluoxetine; sexual experience; homosexual behavior; heterosexual behavior